2021
DOI: 10.1016/j.isci.2021.102436
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes promote ethanol-induced enhancement of intracellular Ca2+ signals through intercellular communication with neurons

Abstract: Ethanol elicits [Ca 2+ ] i signals in astrocytes and neurons using different mechanisms Astrocyte hemichanneldependent ATP release facilitates [Ca 2+ ] i signaling by ethanol Ethanol induces intercellular signaling between astrocytes and neurons Intercellular signaling enhances [Ca 2+ ] i signals in astrocyte and neuron subgroups

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Potentially, the downregulated genes shared between M-type and NR specifically act to lower the threshold and eventually enforce the strongest calcium response to EtOH. In fact, in the coculture configuration in which there is a developmental and constant interaction between neurons and astrocytes, we found that repeated EtOH stimulation evokes reciprocal communication between neuron and astrocytes and enhances their calcium signal intensity through extracellular chemicals ( 24 ). With the astrocyte response type perspective in this study, the enhanced astrocyte calcium signal is the most indicative of M-type characteristics.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Potentially, the downregulated genes shared between M-type and NR specifically act to lower the threshold and eventually enforce the strongest calcium response to EtOH. In fact, in the coculture configuration in which there is a developmental and constant interaction between neurons and astrocytes, we found that repeated EtOH stimulation evokes reciprocal communication between neuron and astrocytes and enhances their calcium signal intensity through extracellular chemicals ( 24 ). With the astrocyte response type perspective in this study, the enhanced astrocyte calcium signal is the most indicative of M-type characteristics.…”
Section: Discussionmentioning
confidence: 98%
“…T-type astrocytes are the most distinctive subgroup from other astrocytes based on common calcium signal-related features of gene expression in both in vitro and in vivo as well as in human samples. Recently, it has been identified that some astrocytes nonresponsive to EtOH at lower doses are responsive at higher doses, while a certain percentage of astrocytes remain persistently nonresponsive at all EtOH doses tested (24). In addition to the characterization of the response-type-specific subtypes in vivo, it will be informative to determine the distinction in NR astrocytes that are persistently nonresponsive at all EtOH doses (i.e., those defined as nonresponsive at the 100 mM dose) compared to NR astrocytes that are recruited to respond to EtOH at higher doses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Signal Enhancement Effect. In the experiment, firstly, the bit error rate after weak signal enhancement in wireless communication network under electromagnetic interference environment is analyzed, and the bit error rate after signal enhancement using this method, reference [5], method, and reference [6] method is compared. The results are shown in Figure 6.…”
Section: Time Domain Waveform Analysis Of Enhancementmentioning
confidence: 99%
“…The linear signal enhancement method is relatively simple, but it still has low performance for nonlinear signals and cannot find the global optimal solution for noise elimination. In addition, because these methods are based on the assumption that the signal is stationary, their effectiveness is generally acceptable, and the actual signal usually has nonstationary statistical characteristics [4][5][6]. Nonlinear methods have become a research hotspot in recent two decades because they can clarify the spectrum and time information in the signal at the same time.…”
Section: Introductionmentioning
confidence: 99%